Chronic Fatigue Syndrome in children population – current knowledge summary - Prylińska, Monika; Skierkowska, Natalia; Topka, Weronika; Kwiatkowska, Małgorzata (Journal of Education, Health and Sport, 2020)
Chronic Fatigue Syndrome/Myalgic Encephalomyelits (CFS/ME) is a chronic disease with complex pathophysiology and unknown etiology. It occurs both in children and adolescents, as well as in adults, with equal frequency. The clinical course is characterized by progressive fatigue, a significant reduction in the body’s efficiency, lack of relief despite rest, and numerous accompanying symptoms. Pathognomonic symptom for PE is the increase in fatigue after physical or mental exertion and the persistence of these symptoms for several hours or days. The basis for effective treatment is primarily non-pharmacological treatment, including determining the optimal balance between physical activity and rest, which is aimed at preventing post-workout fatigue. Pain, insomnia, IO, and other symptoms can be treated with medication. So far, little research has been done on the diagnosis and treatment of this disease in children. This publication aims to summarize the knowledge currently available on the Chronic Fatigue Syndrome in children and adolescents.